Treatment and rehabilitation concepts for patients with addiction and concurrent disorders - Krausz, M.; Vogel, M.; Nikoo, M. (Die Psychiatrie, 2015)
Background: Addiction and concurrent disorders give rise to a major burden of disease in both North America and Europe. However, these two continents have some fundamental differences in regards to the health care system and its funding as well as the types of vulnerable subpopulations to serve. For example, while emergency rooms are often the only available care for patients in the US and Canada due to financial barriers or structural deficits, stepped care approaches and separate rehabilitation systems are more commonplace in Europe. These differences can be observed not only on a transatlantic but also on an intra-European level. These differing attitudes and policies impact on treatment paradigms such as harm reduction, abstinence-based or opioid maintenance treatments etc. Structural components and clinical pathways lead to dissimilarities in access to care services such as detoxification, rehabilitation and community services. The role of primary care as an important treatment interface is much more recognized in Europe. While innovations are ongoing and scientific progress has been made in the treatment of concurrent disorders in recent years, implementing these findings into “real-world practice” has been insufficient so far.
Keywords: Concurrent disorder; mental health; addiction; system of care; rehabilitation